Treatment of an ankle fracture-dislocation using RALCA external fixation. Five-year monitoring - Yaniel Truffin Rodriguez; Osmany Pérez Martínez; Annia L. López Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Ankle fracture dislocation occurs with some frequency in medical practice. The association of a dislocation in ankle fractures modifies its therapeutic approach since the joint should not remain for more than six hours in this situation and therefore emergency surgical treatment will be required. Complications related to the non-reduction of a dislocation in the previously mentioned period of time are known; within these, avascular necrosis of the talus represents the most feared due to the disability it generates. For these reasons, it was decided to present a case that shows the treatment of a fracture -luxation of the right ankle, in a 30-year-old patient, stabilized by using a RALCA mini fixator, which was followed for a period of five years.